Analysis of the relationships between edentulism, periodontal health, body composition, and bone mineral density in elderly women - Ignasiak Z (Dove Medical Press, 2016)
Zofia Ignasiak,1 Malgorzata Radwan-Oczko,2 Krystyna Rozek-Piechura,3 Marta Cholewa,4 Anna Skrzek,5 Tomasz Ignasiak,6 Teresa Slawinska1 1Department of Biostructure, University School of Physical Education, Wroclaw, Poland; 2Department of Periodontology, Wroclaw Medical University, Wroclaw, Poland; 3Department of Physiotherapy and Occupation Therapy in Internal Diseases, University School of Physical Education, Wroclaw, Poland; 4DENTARAMA Dentistry Center, Walbrzych, Poland; 5Department of Physiotherapy and Ocupation Therapy in Motor-System Dysfunction, University School of Physical Education, Wroclaw, Poland; 6Karkonosze State Higher School in Jelenia Gora, Jelenia Gora, Poland Objective: The relationship between bone mineral density (BMD) and tooth loss in conjunction with periodontal disease is not clear. The suggested effects include alteration in bone remodeling rates as well as the multifaceted etiology of edentulism. There is also a question if other body-related variables besides BMD, such as body composition, may be associated with tooth number and general periodontal health. The aim of this study was to evaluate if tooth number and marginal periodontal status are associated with body composition and BMD in a sample of elderly women. Materials and methods: The study involved 91 postmenopausal women. Data included basic anthropometric characteristics, body composition via bioelectrical impedance analysis, and BMD analysis at the distal end of the radial bone of the nondominant arm via peripheral dual-energy X-ray absorptiometry. A dental examination was performed to assess tooth number, periodontal pocket depth (PD), and gingival bleeding. Results: In nonosteoporotic women, a significant positive correlation was found between BMD and lean body mass, total body water, and muscle mass. The indicators of bone metabolism correlated negatively with PD. Such relationships did not appear in osteoporotic women. In both groups, basic anthropometric characteristics and body composition were significantly and positively correlated with PD and bleeding on probing. Conclusion: The results suggest that body composition and BMD are not significantly correlated with tooth number and gingival bleeding. Keywords: tooth number, bone mineral density, fat mass, lean body mass